Ibarra fire department: depression through the CES-D inventory - Cadena Povea, Henry (Revista Ecos de la Academia, 2021)
The research aimed at detecting depression in the members of the Ibarra City Fire Department through the Depression Scale of the Epistemological Studies Center (CES-D) adapted to the Ecuadorian context. The study was carried out with a population sample of 105 firefighters (26 women and 79 men) who are members of the different Fire Station of the city of Ibarra. The study was descriptive under the analytical-synthetic method, with a non-experimental, cross-sectional design, with a quantitative and psychometric approach. After applying the test, the presence of depression was observed in firefighters, when analyzing the difference in results in terms of gender, it was found that men presented more depressive indexes. The level of suffering of this pathology in administrative and operational personnel was also evaluated, resulting in a higher percentage of depression in operating personnel. These results determine worrisome and considerable risks in the activities they carry out, which is why they are significantly affected psychologically and emotionally.